Analysis of ergonomic occupational accidents and near misses in a large Belgian university hospital. Issue 6 (2nd November 2022) - Fraeyman, Norbert; de Bacquer, Dirk; Clays, Els; Fiers, Tom; Godderis, Lode; Verhaeghe, Rik; Viaene, Leen; Mortier, Eric
ABSTRACT: Introduction: Health-care organizations are facing a high burden of ergonomic occupational accidents, and prevention is a continuous point of interest. In this manuscript, we describe the characteristics of ergonomic accidents in a large Belgian university hospital and discuss the value of near misses. Methods: Combining databases, we identified the frequency [number of accidents × 10 6 hours worked per year], severity (number of days off work × 10 3 hours worked per year), and profile of the victims of occupational ergonomic accidents (with absence from work) or incidents or near-misses (without absence from work). Ergonomic accidents and incidents include slips, trips, falls, injurious body movements, overexertion, and handling heavy weights. Results: In a period of 23 years, we noticed a significant decrease in the frequency of ergonomic accidents (from about 7 to about 4 standard units), without changes in the severity. The decrease in the frequency of accidents is mirrored by an increase in the frequency of incidents (from about 4 to about 6 standard units). Female and older employees are more vulnerable to accidents, and the frequency was between two and four times higher for employees mostly involved in manual tasks compared to employees mostly involved in managerial tasks. The profile of the victims and the causes of accidents and incidents were identical. Conclusion: Although it is premature to assume a cause–consequence relationship between incidents and accidents, it is tempting to speculate that the increased ratio of the frequencies of incidents over accidents might be one of the variables reflecting the adequacy of preventive measures and the growth of safety behavior.